Predation of the fiddler crab, Minuca osa (Brachyura: Ocypodidae), by Eudocimus albus (Pelecaniformes: Threskiornithidae) from Ponuga, Veraguas, Panama - Lombardo-González, Roberto C. (2023)
Numerous avian species prey on fiddler crabs, yet the ecological relationships involving Minuca osa crabs and their predators remain poorly understood. We report the first documented cases of M. osa predation by White Ibis, Eudocimus albus. Three distinct predation events were observed: June 3rd, 2021, November 10th, 2022, and November 25th, 2022, in the Gulf of Montijo, Veraguas, Panama. Examination of E. albus feces provided confirmation of such predator-prey interaction.